The Implication of Corruption to Nigeria’s Internal Security: Insights from Selected Security Agencies - Yagboyaju, Dhikru Adewale (Scientia Militaria - South African Journal of Military Studies, 2023)
The research on which this article reports, analysed corruption as a major threat to Nigeria’s internal security. Studies have examined dimensions of corruption and their effects on security in the country, but this article sets out to analyse selected forms of abuse in the operations of two security agencies, the Army and Prison Services, in Nigeria’s Ministries of Defence, and Interior respectively. The two represent military and paramilitary services in Nigeria, but they have overlapping duties and functions with other security agencies like the police, for example. Data is drawn from secondary sources for the conceptual and theoretical sections of the article. This is complemented by primary data from events analyses, especially from public hearings concerning the selected security agencies in Nigeria. A combination of the structural theory and the ecological approach is deployed for the article’s analytic frame. The article finds out that the two agencies selected for study reflect the prevalence of corruption in several sectors of Nigeria’s internal security architecture. It recommends a head-on combating of corruption which involves diligent closure of on-going cases of security breaches and corruption as well as the involvement of volunteers and communities.